(2w-3)+w+(2w-3)+w=26

Simple and best practice solution for (2w-3)+w+(2w-3)+w=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2w-3)+w+(2w-3)+w=26 equation:


Simplifying
(2w + -3) + w + (2w + -3) + w = 26

Reorder the terms:
(-3 + 2w) + w + (2w + -3) + w = 26

Remove parenthesis around (-3 + 2w)
-3 + 2w + w + (2w + -3) + w = 26

Reorder the terms:
-3 + 2w + w + (-3 + 2w) + w = 26

Remove parenthesis around (-3 + 2w)
-3 + 2w + w + -3 + 2w + w = 26

Reorder the terms:
-3 + -3 + 2w + w + 2w + w = 26

Combine like terms: -3 + -3 = -6
-6 + 2w + w + 2w + w = 26

Combine like terms: 2w + w = 3w
-6 + 3w + 2w + w = 26

Combine like terms: 3w + 2w = 5w
-6 + 5w + w = 26

Combine like terms: 5w + w = 6w
-6 + 6w = 26

Solving
-6 + 6w = 26

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 6w = 26 + 6

Combine like terms: -6 + 6 = 0
0 + 6w = 26 + 6
6w = 26 + 6

Combine like terms: 26 + 6 = 32
6w = 32

Divide each side by '6'.
w = 5.333333333

Simplifying
w = 5.333333333

See similar equations:

| 7=4x-9 | | .5y+2=0.8y-0.3y | | 64x-48=-6x-22 | | 3(2x+5)=30-4x | | 8j=16 | | 2x*4(x-3)(x+3)=8x*x-3 | | -(7-4x)=-15 | | c-35.95=154.05 | | 430-x=155 | | 3(2x+1)+2(4x+2)=35 | | 3(x-7)=2(10+x) | | (x-7)=2(10+x) | | 6x^2-7=11 | | 2x+18=5x+9 | | 5X^2+10X^2=-7+X+X^2 | | (1000*25)-(1000*x)=5000 | | X(335-2x)=1150 | | 12+3108873456= | | -7x-4(-2+7)=-39 | | (X-3)2=13 | | X(335-2x)=0 | | 2x+y=335 | | x-y=23+2x | | 8x+4=5x-14 | | 0.4r-0.5=5.3r+0.7 | | 20-4x=6x-3x+11-3 | | (18x-24y)(18x-24y)= | | (18x-24y)2= | | Y-x(3)+2x+0.5=0 | | x=0.5y-5 | | 0.7(x-5)=5.2-3.7x | | 8x-(5)=5x-(2) |

Equations solver categories